PO 111 - Síndrome QT longo, silencioso e potencialmente fatal - case report - Santos, Olga; Rosinha, Daniela; Gonçalves, Nádia; Maia, Paulo (Journal of the Portuguese Society of Anesthesiology, 2023)
x